Health and well-being of nursing workers: a bibliometric study - Passos, Inês Francisca; Freitas, Rodrigo Randow de (Brazilian Journal of Production Engineering, 2025)
This article presents a bibliometric survey in the context of nursing. The objective is to find themes addressed in research on fatigue, as well as its relationship with well-being at work in the context of nursing occupation. The methodology adopted was a search in the CAPES Periodicals Portal database, with subsequent reading of the abstracts and selection of articles. From the selection of articles, a word cloud was generated that indicated the main themes addressed in the articles that meet the study theme. Therefore, in the evaluation of the articles, these results were taken into consideration for the approach, including in future studies.
Keywords: Fatigue; Well-being; Bibliometrics